Production of Biosurfactant by Locally Isolated Thermophilic Facultatively Anaerobic Bacteria strain B160 - Daud, Nunizawati; Yahya, Adibah; Md Salleh, Madihah; Suhaimi, Norazurah; Chan, Hui Xuan (2007)

(untitled)
Bacteria strain B160 was found to be the most potential biosurfactant producer amongst others. This was indicated by its ability to show collapse against the oil surface and most importantly its ability to show higher reduction of surface tension (30.6%) against medium. The production of biosurfactant by strain B160 was enhanced under facultatively anaerobic condition. This was confirmed by the higher Pmax obtained from the culture grown under facultative (7.0 g/l) compared to that obtained under aerobic (0.9 g/l) conditions. The crude biosurfactant was isolated from bacteria cell-free broth, by acid â€“precipitation and followed by solvent extraction. Chloroform-methanol (2:1) was showed to be the best solvent system found for the extraction with the maximum recovery of 7.0 g/L compared to Chloroform:MTBE (1:1)(6.1g/L). The ability of strain B160 to grow and produce biosurfactant on different carbon sources, temperatures and pH under facultatively anaerobic condition was studied. In this study, the biosurfactat productivity was enhanced 6.2 folds in cultures grown in a medium supplemented with 2.0 % (w/v) fructose adjusted to pH 7.0 and incubated at 50Âº. The productivity at the optimum condition (1.19 g/L/h) was approximately 6.2 folds higher compared to the initial productivity (0.19 g/L/h).